ПЕДАГОГИКАЛЫҚ ЖОҚАРЫ ОҚЫЎ ОРЫНЛАРЫНДА ИНФОРМАТИКА АРНАЎЛЫ КУРС МАЗМУНЫНЫҢ МЕТОДИКАЛЫҚ ТИЙКАРЛАРЫ - Ильясова, З.К. (FAN va JAMIYAT, 2021)
In the article, the methodological foundations of the essence of the special course "Informatics" are prepared for the training of teachers for the systems of continuous education. And also, the tasks and requirements for studying the computer science course required for mastering knowledge, skills, and the ability of students are defined.